Defining gaps in PrEP delivery for pregnant and breastfeeding women in high burden settings using an implementation science framework - Pintye, Jillian (Lancet HIV, 2020)
Pregnancy is a period of high HIV acquisition risk for African women, and pregnant women who become acutely infected with HIV account for up to one-third of vertical HIV transmissions. To protect women and eliminate vertical transmission, the World Health Organization recommends offering oral tenofovir-based pre-exposure prophylaxis (PrEP) to HIV-negative pregnant and postpartum women with substantial HIV acquisition risk. PrEP implementation for pregnant and postpartum women lags behind other high-risk populations. Unique considerations for PrEP implementation arise during pregnancy and postpartum, including integration of provider training, clinical delivery, and monitoring PrEP exposure and outcomes within existing maternal health systems, yet few implementation data are available to generate evidence in this context. In this Viewpoint, we examine current PrEP delivery among pregnant and postpartum African women, identify gaps in evidence according to the RE-AIM framework, and offer recommendations to guide the implementation science research agenda to optimize PrEP for these populations.